Flourishing lives : exploring natural law liberalism / Gary Chartier. - Chartier, Gary (Cambridge University Press, 2019)
This book elaborates, illuminates, and illustrates a confident and attractive account of social and political liberalism in light of a rich understanding of flourishing and fulfilment rooted in a version of natural law theory. Examining issues in ethics, law, and politics - including consumer responsibility, the assignment of grades by teachers, deception by lawyers, war and empire, and the use of victim-impact statements in parole decisions - Gary Chartier shows how natural law theory can effectively support pluralism, diversity, social equality, integrity, peace, and freedom.